Beta‐Sheet‐Forming, Self‐Assembled Peptide Nanomaterials towards Optical, Energy, and Healthcare Applications. Issue 30 (30th April 2015) - Kim, Sungjin; Kim, Jae Hong; Lee, Joon Seok; Park, Chan Beum
<x xml:space="preserve">Abstract</x> Peptide self‐assembly is an attractive route for the synthesis of intricate organic nanostructures that possess remarkable structural variety and biocompatibility. Recent studies on peptide‐based, self‐assembled materials have expanded beyond the construction of high‐order architectures; they are now reporting new functional materials that have application in the emerging fields such as artificial photosynthesis and rechargeable batteries. Nevertheless, there have been few reviews particularly concentrating on such versatile, emerging applications. Herein, recent advances in the synthesis of self‐assembled peptide nanomaterials (e.g., cross β‐sheet‐based amyloid nanostructures, peptide amphiphiles) are selectively reviewed and their new applications in diverse, interdisciplinary fields are described, ranging from optics and energy storage/conversion to healthcare. The applications of peptide‐based self‐assembled materials in unconventional fields are also highlighted, such as photoluminescent peptide nanostructures, artificial photosynthetic peptide nanomaterials, and lithium‐ion battery components. The relation of such functional materials to the rapidly progressing biomedical applications of peptide self‐assembly, which include biosensors/chips and regenerative medicine, are discussed. The combination of strategies shown in these applications would further promote the discovery of novel, functional, small materials.